ترا با هلوصأ و هقفلالةغل - Nurlaila, Nurlaila (JURIS (Jurnal Ilmiah Syariah), 2012)
Arabic language has close relationship with the fiqh (Islamic jurisprudence) and ushul fiqh (source methodology), because both of the sciences are derived from al-Quran and al-Hadith. Ulama make it as one of the ultimate requirements for those who wish to explore fiqh and ushul fiqh, because there are many differences of syar'i laws as a result of language problems. So that, understanding of arabic is compulsory for those who want to understand the laws of Allah.